Training in primary care paediatrics: The role of entrustable professional activities - C. Villaizán Pérez; M. Aparicio Rodrigo; F. Fehr (Global Pediatrics)
Primary care paediatrics is practiced throughout the countries of Europe with different structures of health care systems and identities of care providers. The best way to guarantee that paediatricians are competently trained and provide high quality care to children and adolescents in primary care is a flexible and comprehensive training program based on practice and demonstration of acquired competencies. Entrustable professional activities represent a significant step toward improving the training and assessment of future healthcare professionals. It may constitute a model that unifies the training standards in primary care and community paediatrics.